2017
DOI: 10.1061/(asce)be.1943-5592.0001086
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identification of a Concrete-Filled Steel Tubular Arch Bridge via Ambient Vibration Test Data

Abstract: Structural identification (St-Id) is an effective structural evaluation approach for health monitoring and performance-based engineering. However, various uncertainties may significantly influence the reliability of St-Id. This paper presents ambient vibration measurements to develop a baseline model for a newly constructed arch bridge over Hongshui River in Guangxi, China. In this study, modal parameter identification was performed using the random decrement (RD) technique together with the complex mode indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Particularly, in the work done by Zhou et al. ( 2017b ), a GA is also applied to minimize the difference between numerical and experimental data related to the static response of the bridge. Useful insights about the application of a GA for model updating based on static or dynamic tests are reported by Chisari et al.…”
Section: Computational Intelligence In Shmmentioning
confidence: 99%
“…Particularly, in the work done by Zhou et al. ( 2017b ), a GA is also applied to minimize the difference between numerical and experimental data related to the static response of the bridge. Useful insights about the application of a GA for model updating based on static or dynamic tests are reported by Chisari et al.…”
Section: Computational Intelligence In Shmmentioning
confidence: 99%
“…A description of the basic steps to identify dynamic parameters of the structure could be found in [32]. They included the creation of a priori models, vibration testing, post-processing of received data, validation and calibration, and also the utilization of a numerical model in some cases [33]. During the experimental study, two basic methods could be distinguished to find out the modal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…With the purpose of improve the computational efficiency, some hybrid methods were proposed with the approach of roughly search with swarm intelligence algorithms till close to the solution, then fine search with guided methods to the optimal. The genetic annealing hybrid algorithm, combining simple GA and simulated annealing algorithm, was proposed for structural identification in large-scale arch bridge [34]. The results showed that the hybrid identification method exhibited the best performance in accuracy and efficiency of results in comparison with simple GA and simulated annealing algorithm.…”
Section: Introductionmentioning
confidence: 99%